Bridging classical and quantum mechanics. (28th September 2016) - Haddad, D; Seifert, F; Chao, L S; Li, S; Newell, D B; Pratt, J R; Williams, C; Schlamminger, S
Abstract: Using a watt balance and a frequency comb, a mass-energy equivalence is derived. The watt balance compares mechanical power measured in terms of the meter, the second, and the kilogram to electrical power measured in terms of the volt and the ohm. A direct link between mechanical action and the Planck constant is established by the practical realization of the electrical units derived from the Josephson and the quantum Hall effects. By using frequency combs to measure velocities and acceleration of gravity, the unit of mass can be realized from a set of three defining constants: the Planck constant h, the speed of light c, and the hyperfine splitting frequency of 133 Cs.